Self-Efficacy Siswa dalam Mempelajari Matematika Terkait dengan Persepsi Siswa pada Perilaku Interpersonal Guru - Betharia Rosalina; Sri Tiatri (Provitae: Jurnal Psikologi Pendidikan, 2012)
The number of complaints and the phenomenon of Mathematics NationalExamination indicated a lack of belief for facing it. Belief is needed to face acertain task is known as self-efficacy (Bandura, 1997). There are many sources that can affect someone’s self-efficacy, namely internal and external sources. For having high self-efficacy through the National Examination, especially in mathematic as Bandura’s theory (1997), students do not only need belief that comes from their abilities or experiences (internal sources), but also from the presences and roles that are received by the mathematic teachers, parents, friends, and others (external sources). This study was aimed to assess whether there is a relationship between student’s perceptions of teacher’s interpersonal behavior with their self-efficacy through the Mathematics National Examination. This research used quantitative method, involved 109 students of ninth grade in Junior High School which is located in West Jakarta. By using a correlation test, it was found there was a relationship between students’ self-efficacy in mathematic with students’ perceptions of teacher’s interpersonal behavior in proximity (cooperation-opposition), but did not reveal any relationship with students’ perceptions of teacher’s interpersonal in influence (dominance-submission). Keywords: perception, teacher’s interpersonal behavior, self-efficacy, mathematics